KAJIAN KERUSAKAN LINGKUNGAN AKIBAT PENAMBANGAN LEMPUNG DI DESA SIDOREJO KECAMATAN GODEAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - , IKA ARSI ANAFIATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was carried out at Sidorejo village, Godean subdistrict, Sleman district Daerah Istimewa Yogyakarta. The objectives of this research was to: 1) determine the level of environmental damage caused by clay mining, 2) analyze land improvement of land in clays mined lands, 3) develop guidance reclamation and direction mining technique effort to land the improvement that can be recovered in accordance with potential properly and 4) determine the social factors give an influences of mining activities. The method used was a survey method and scoring. Parameters are assessed in determining the extent of environmental damage caused by mining excavation is borders, boundary depth of excavation, foundation excavation relief, cliff slope limit excavation, quarry wall height, depth of groundwater advance, springs, road conditions, vegetation cover, reclamation efforts, the old mine, miner income, education level and live miners. Sampling was purposive sampling method. Data analysis methods to perform land reclamation in mining areas of research include: an empirical analysis, analysis of spatial ecology, and descriptive analysis. The results of environmental damage level caused by clay mining in the Sidorejo village are two levels. There are moderate and heavy damage. Heavy environmental damage level are located on 7 (seven) mining sites of Kleben (location 1), Jering (3 location), Mloyorejo (location 6 and 7) and Kwagon locations 8 , 9 and 10). Heavy environmental damage level is on the value of 47.6 to 58.8. While the moderate environmental damage level is located in three mining sites in Kleben (2 locations) and Jering (locations 4 and 5) are on the value of 36.4 to 47.6. Mining techniques guidance use side hill type and contour mining. Reclamation uses a combination of technique and vegetative reclamation. The effect of social factors in the Sidorejo village mining activity for moderate environmental damage level is the level of education and for the heavy environmental damage level is mining periode.